2011
DOI: 10.1094/pdis-09-10-0620
|View full text |Cite
|
Sign up to set email alerts
|

Control of Common Bunt in Organic Wheat

Abstract: Common bunt, caused by the seedborne and soilborne pathogens Tilletia caries and T. laevis, has re-emerged as a major disease in organic wheat. In conventional agriculture, common bunt is routinely managed with the use of synthetic chemical seed treatments. For this reason, common bunt is a relatively unimportant disease in conventional agriculture. However, since synthetic chemical inputs are prohibited in organic agriculture, common bunt is a major threat once more in organic wheat and seed production. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Thus, they are not suitable for direct use in wheat production but can serve as donors of resistance genes in breeding programs (Ruzgas and Liatukas 2009;Matanguihan et al 2011). In compliance with this observation, the present study showed that bunt incidence was positively correlated with yield components (spike length, spikelet number and grain number in the main spike) in the progeny of 'Svilena' × A-38b cross.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Thus, they are not suitable for direct use in wheat production but can serve as donors of resistance genes in breeding programs (Ruzgas and Liatukas 2009;Matanguihan et al 2011). In compliance with this observation, the present study showed that bunt incidence was positively correlated with yield components (spike length, spikelet number and grain number in the main spike) in the progeny of 'Svilena' × A-38b cross.…”
Section: Discussionsupporting
confidence: 74%
“…T. laevis JG Kühn). T. caries is more prevalent in North-Western Europe, while T. foetida is more common to Eastern Europe (Matanguihan et al 2011), including Bulgaria (Atanassov 1929;Dodov and Todorova 1974).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In managing seed-borne diseases, resistant varieties play a crucial role, and therefore efforts have been made to identify sources of disease resistance against, e.g. common bunt (Dumalasová and Bartoš 2006;Gaudet et al 2007;Matanguihan et al 2011) and black point (Conner and Davidson 1988;Christopher et al 2007) in wheat. Wheat material originating from CIMMYT has been evaluated in Canada and limited resistance was found (Gaudet et al 1995).…”
Section: Discussionmentioning
confidence: 99%